Siderophore and haem iron use by Tritrichomonas foetus - Sutak, Robert; Chamot, Christophe; Tachezy, Jan; Camadro, Jean-Michel; Lesuisse, Emmanuel (Microbiology (Reading, England), 2004)
The ability of the parasitic flagellate Tritrichomonas foetus to use various iron sources for its physiological requirements was studied. The siderophores ferrioxamine B, ferrichrome, triacetylfusarinine, coprogen, enterobactin and pyoverdine sustained growth of the cells under iron-limited conditions, and siderophore iron was incorporated into the major iron protein of T. foetus, ferredoxin. The kinetics of siderophore uptake by the cells indicated that a non-saturable transport is involved, unlike the uptake of a ferrous salt. Siderophore uptake by the cells did not involve extracellular reductive dissociation of the ferric chelates, although T. foetus cells had some ferrireductase activity on ferric citrate. Fluorescent analogues of siderophores were used to show that the siderophores taken up by the cells were in small intracellular vesicles. The fluorescence emission maximum of pyoverdine in these intracellular vesicles shifted from 460 nm to 530 nm, indicating a very acidic environment. The results suggest that a wide range of chemically unrelated siderophores can be taken up non-specifically and efficiently used by T. foetus; the mechanism involved may be pinocytosis and removal of the iron from the siderophores in acidic intracellular vesicles. Haemin also sustained the growth of T. foetus cells under iron-limited conditions. The use of haemin iron by the cells probably involves haem oxygenase, since traces of biliverdin were found in the medium when haemin was the iron source. The iron uptake and ferrireductase activities of the cells do not seem to be regulated by the amounts of iron and copper in the growth medium.
Keywords: železo; pinocytóza; Transport Vesicles; Iron; hem; Pinocytosis; oxidace-redukce; zvířata; Culture Media; transportní vezikuly; kultivační média; Siderophores; Hydrogen-Ion Concentration; Oxidation-Reduction; siderofory; Animals; Tritrichomonas foetus; koncentrace vodíkových iontů; Heme